Quality Improvement on SMEs: Trend and Visualization with Bibliometric Analysis - Abdurrahman Rahim Thaha (PT Mattawang Mediatama Solution, 2022)
The purpose of this study is to discover the mapping and research trends of quality improvement in Small and Medium-sized Enterprises (SMEs) that Scopus index. A bibliometric analysis was conducted in this study from 1992 to mid-2022. The keywords quality improvement and SMEs are used in the title, abstract, and keywords for further filtering and screening manually. The analysis results yielded 114 relevant articles with the peak publications in 2019. India became the country with the highest quantity of publications, and the United Kingdom became the country with the most citations. Three cluster topics formed: SMEs' adaptation to consumer desires with quality processes and products, companies' challenges in accommodating the market without sacrificing product quality, and impact quality management to improve community outcomes with standardization. This paper provides an updated overview of research related to quality improvement and SMEs.